A Qualitative Analysis of the Phenomenon of Lonely BIM in Infrastructure Projects - Ahmad Rifqy Zein; Ferry Hermawan; Jati Utomo Dwi Hatmoko (Diponegoro University, 2025)
The integration of Building Information Modeling (BIM) in construction faces challenges due to differing approaches from stakeholders. This study emphasizes the need for practical improvements in BIM implementation in Indonesia, particularly in managerial aspects. By identifying the factors causing isolated BIM usage ('Lonely BIM'), this research provides actionable strategies to promote better collaboration, enhance stakeholder coordination, and streamline BIM processes in infrastructure projects. These insights aim to improve efficiency, reduce project delays, and encourage wider adoption of BIM, ensuring more consistent and integrated digital construction practices across the industry. Using qualitative methods, interviews and project data were analyzed with ATLAS.ti software. The factors identified include organizational culture, with the top rank being workplace culture, software/hardware investment with the top rank being software/hardware procurement, human resources factors with the top rank being the lack of human resources and support, skill disparity factors with the top rank being stakeholder BIM capability, technological gaps among stakeholders, communication constraints with the top rank being the effectiveness of coordination and communication methods, and the factor of owner demands, where the majority do not require BIM. These results identify important factors influencing BIM isolation and offer insights for the construction industry to overcome these barriers.